Terminating 3F2(2) and Some Identities for 2F2 - Hernández-Galeana, A.; López-Vázquez, R; López-Bonilla, J. (Journal of Institute of Science and Technology, 2015)
The Petkovsek-Wilf-Zeilberger’s algorithm permits to give a simple proof of the Rathie-Pogany’s identity for the hypergeometric function 2F2. Journal of Institute of Science and Technology, 2015, 20(1): 123-126